Islamophobia or Islamophobias: Towards Developing A Process Model - Iqbal, Zafar (Islamic Studies, 2010)
This paper attempts to explore Islamophobia and assumes it to be a composite and multi-dimensional construct with its epistemic/symbolic dimensions having different connotations, the meaning of which needs to be distilled through its explication into less abstract dimensions. This study assumes Islamophobia to be a mediated construct which is variegated; hence, it appears as a corpus constituted of Islamophobias. This exploration attempts to conceptualize and operationalize the said construct so that its nexus with the media and other social antecedents can be empirically examined.